Pengukuran Kinerja Supply Chain Susu Kental Manis Menggunakan Metode SCOR dan AHP - Monica Permatasari; Santika Sari (Universitas Teuku Umar, 2021)
PT Frisian Flag Indonesia is a manufacturing company in Jakarta which is engaged in the milk processing industry. PT Frisian Flag Indonesia has not implemented a detailed performance measurement system and only applies a measure of the effectiveness of company performance. The need for Supply chain performance measurement to be able to find out the results of the Supply chain performance of sweetened condensed milk and make improvements to activities that are not optimal. The method used in this research is the AHP-SCOR method and to determine the Supply chain performance score, the Key Performance Indicator (KPI) measurement is used. The results showed 27 valid KPIs using the Snorm De Boer normalization process and the values obtained were: plan was 88,83, make was 93,79, source was 84,545, delivery was 88,149, Return was 38,53. The results of the SCOR model are 81.45. The need for improvements that prioritize performance with the smallest value, namely return.